Clinical outcomes of increased regional amyloid uptake in patients with subthreshold global amyloid levels. (1st February 2022) - Kim, Jaeho; Choe, Yeongsim; Park, Yuhyun; Kim, Yeshin; Kim, Junpyo; Seo, Younghoon; Jang, Hyemin; Kim, Hee Jin; Na, Duk L.; Cho, Soo‐Jin; Moon, Seung Hwan
Abstract: Background: Although the standardized uptake value ratio (SUVR) method is objective and simple, cut‐off optimization using global SUVR values may not reflect focal increased uptake in the cerebrum. The present study investigated clinical and neuroimaging characteristics according to regionally increased β‐amyloid (Aβ) uptake and global Aβ status. Method: We recruited 973 patients with Alzheimer's disease ‐related cognitive impairment (ADCI). All patients underwent neuropsychological tests and 501 18 F‐florbetaben (FBB) amyloid positron emission tomography (PET) and 472 18 F‐flutemetamol (FMM) PET. Each PET scan was assessed in 10 regions (frontal, temporal, parietal, posterior cingulate, and striatum) by regional quantitative SUVR‐based cutoff values for each region using an iterative outlier approach. Result: A total of 64 (6.6%) subjects showed increased regional Aβ uptake with subthreshold global Aβ status [focal (+) and global (‐) Aβ group, F(+)G(‐) group]. The F(+)G(‐) group showed worse performance in memory impairment ( P < 0.001) and greater hippocampal atrophy ( P = 0.024) but not global cognition and cortical thickness, compared to those in the F(‐)G(‐). Participants with diffuse Aβ involvement in the whole region [diffuse (+) and global (+) Aβ group, D(+)G(+)] showed worse neuropsychological ( P = 0.008‐0.042) and neuroimaging features ( P <0.015) than those with focal Aβ involvement F(+)G(+). Conclusion: ] Our findings suggest that individuals show distinctive clinical outcomes according to regionally increased Aβ uptake and global Aβ status. Thus, clinicians should pay more attention to regional increased Aβ uptake in addition to global Aβ status.